Relevansi Konsep Mondok untuk Mengaji dan Membina Akhlakul Karimah KH. Zaini Mun’im dalam Kontruksi Fiqh Moderat di Pesantren - Akhmad Pathollah; Muhalli Muhalli; Badrul Mudarris (Ambarsa : Jurnal Pendidikan Islam, 2024)
In several religious practices, Fiqh is often used as a basis for intolerance, discrimination and practices of social injustice, even conservatism and radicalism in society. This matter certainly shows the paradoxical nature of Islamic religious practice, where Islam has a vision of rahmatan lil'alamin, but it is being the root of the existence of squabbling in society. Departing from this problem, this research aims to explain the relevance of the concept of study for reciting the Qur’an and developing good the morals of KH. Zaini Mun'im in the construction of moderate Fiqh in Pesantren. This research is qualitative research with the type of library study. The analysis used is descriptive analysis and content analysis. Test the validity of the data by using intertextual source triangulation. The results of this research are; firstly, the existence of the concept of study for reciting the Qur’an and developing good morals is an affirmation of the aim that every process of reciting leads to construct good morals, towards Allah SWT, and fellow or human beings; secondly, in turn, tafaqquh or depth of understanding of Islamic religious teachings, especially Fiqh, will be oriented towards building good social relations in society. This research is expected to contribute to the construction of moderate Fiqh that is able to accomodate the differences in society.